2016
DOI: 10.1097/cej.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

β-Blocker use and mortality in cancer patients: systematic review and meta-analysis of observational studies

Abstract: A number of epidemiologic studies have attempted to link the use of β blockers to mortality in cancer patients, but their findings have been inconclusive. A meta-analysis was carried out to derive a more precise estimation. Relevant studies were identified by searching PubMed and EMBASE to May 2015. We calculated the summary hazard ratios (HRs) and 95% confidence intervals (CIs) using random-effects models. Twenty cohort studies and four case-control studies involving 76 538 participants were included. The ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 54 publications
(111 reference statements)
0
33
0
Order By: Relevance
“…Zhong et al performed a systematic review and meta-analysis of observational studies of beta-blocker use and cancer mortality [77]. They identified 24 relevant studies that had reported results by May 2015, involving 76 538 patients.…”
Section: Human Datamentioning
confidence: 99%
“…Zhong et al performed a systematic review and meta-analysis of observational studies of beta-blocker use and cancer mortality [77]. They identified 24 relevant studies that had reported results by May 2015, involving 76 538 patients.…”
Section: Human Datamentioning
confidence: 99%
“…Indeed, this analysis objectively confirmed the latest development in this topic. All the previous three articles drew a conclusion that beta-blocker use could prolong the survival of cancer patients, 44 46 but our current analysis showed an opposite conclusion that there is generally no relationship between beta-blocker use and cancer prognosis.…”
Section: Discussionmentioning
confidence: 53%
“…Prolonged BB exposure can also lead to β receptor upregulation, hampering the effectiveness of BB (10). This phenomenon has been demonstrated in observational studies where post-diagnostic BB use was associated with significant improvements in survival outcomes compared to pre-diagnostic BB use (27). In the present study, the sample of patients on non-selective BB was insufficient for an appropriately powered subgroup analysis (n = 51), and data on the length of prior BB use was not available.…”
Section: Discussionmentioning
confidence: 97%